Prevention of postoperative lower extremity deep vein thrombosis (Literature Review) (Eurasian Medical Research Periodical, 2024)
Revelance. Acute thrombosis of the inferior vena cava system is a dangerous disease threatening the development of pulmonary embolism (TELA), the mortality rate of which reaches 30% [1]. Among the etiologic factors of this severe complication, postoperative venous thrombosis occupies an important place, the prevention of which eliminates not only the danger of TELA, but also chronic venous insufficiency in the distant period. How often does thrombosis complicate the course of the postoperative period? How real is this danger? The answer to these questions depends on the attitude of surgeons to the problem of postoperative venous thromboembolic complications and their activity in carrying out the necessary preventive measures. The data on the incidence of postoperative thrombosis are quite contradictory [3, 4]. If based only on clinical data, it seems to be insignificant. At the same time, deep vein thrombosis of the lower limbs occurring after various surgical interventions is characterized by asymptomatic course. Sometimes the first and only manifestation of such thrombosis may be fatal TELA. This circumstance explains the extremely high percentage of massive embolism undiagnosed in life (up to 50% and more).